Representing Local Cultural Identity in The Sarafal Anam Oral Tradition: A Semiotic Study of The Bengkulu Tengah Community - Perina Anita Sari; Martha Heriniazwi Dianthi; Dilmai Putra (Journal of Multidisciplinary Research, 2026)
This study aims to analyze the representation of cultural identity contained in the Bishahri poem within the Sarafal Anam tradition of the Bengkulu Tengah community. Sarafal Anam is a religious oral tradition that developed as a result of the acculturation between Islamic teachings and local cultural practices. The tradition involves the recitation of prayers and poetic praises dedicated to Prophet Muhammad, which are commonly performed during social and religious ceremonies such as childbirth celebrations, family thanksgiving events, and Islamic religious commemorations. This research applies a qualitative approach using Roland Barthes’ semiotic analysis, which focuses on three levels of meaning: denotation, connotation, and myth. The research data were obtained through textual analysis of the Bishahri poem, interviews with traditional leaders, religious figures, and Sarafal Anam practitioners, as well as documentation of the tradition. The findings indicate that at the denotative level, the poem describes the birth of Prophet Muhammad through symbols such as light, the full moon, and noble attributes. At the connotative level, these symbols signify spiritual guidance, moral perfection, and hopes for blessings in human life. At the mythological level, these symbols construct a collective belief that Prophet Muhammad represents the ultimate source of spiritual and moral light for humanity. Furthermore, the Sarafal Anam tradition functions not only as a religious ritual but also as a medium for representing the cultural identity of the Bengkulu Tengah community, strengthening social solidarity and preserving local cultural values transmitted across generations.